Pembelajaran Integratif Pendidikan Agama Islam (PAI) di Madrasah Berbasis Pesantren: Integrative Learning of Islamic Religious Education (PAI) in Pesantren-Based Madrasah - Mukni’ah Mukni’ah (Fenomena, 2014)
In the context of Muslims’ life, the teaching of Islamic religion should be the basis of the education system. Islamic boarding school (pesantren) is one form of those Islamic education systems. However, it will be unwise if we depend only on one system, so that we need an integrative system as the Islamic boarding school’s responsibility to society. The Islamic Education curriculum design at Syarifudin Islamic boarding school is designed to fulfill the needs of society while still maintaining the Islamic boarding school characters. The curriculum at the Islamic boarding school is integrated and classified into two types, namely formal education curriculum and Islamic boarding school curriculum or intra and extra-curricular. Moreover, the main content of the curriculum for formal education applies the Integrated Education System between the Ministry of Education and the Ministry of Religious Affairs of Indonesia. Meanwhile, the Islamic basic school (Madrasah Diniyah) uses a classic curriculum of the yellow book (kitab kuning) with Indonesian as the teaching instruction. Dalam konteks kehidupan muslim, pengajaran agama Islam seharusnya menjadi dasar sistem pendidikan. Pesantren adalah salah satu bentuk sistem pendidikan Islam tersebut. Namun, tidak bijaksana jika kita hanya bergantung pada satu sistem, sehingga diperlukan sistem integratif sebagai tanggung jawab pesantren terhadap masyarakat. Desain kurikulum Pendidikan Agama Islam di Pesantren Syarifudin dirancang untuk memenuhi kebutuhan masyarakat sambil tetap mempertahankan karakter pesantren. Kurikulum di pesantren terintegrasi dan diklasifikasikan menjadi dua jenis, yaitu kurikulum pendidikan formal dan kurikulum pesantren atau intra dan ekstrakurikuler. Selain itu, muatan utama kurikulum untuk pendidikan formal menerapkan Sistem Pendidikan Terpadu antara Kementerian Pendidikan dan Kementerian Agama Indonesia. Sementara itu, madrasah diniyah (sekolah dasar Islam) menggunakan kurikulum klasik kitab kuning dengan bahasa Indonesia sebagai bahasa pengantar.